2016
DOI: 10.3847/0004-637x/829/2/109
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of the Early Light Curves of Type Iip Supernovae

Abstract: The early rise of Type IIP supernovae (SN IIP) provides important information for constraining the properties of their progenitors. This can, in turn, be compared to pre-explosion imaging constraints and stellar models to develop a more complete picture of how massive stars evolve and end their lives. Using the SuperNova Explosion Code (SNEC), we model the first 40 days of SNe IIP to better understand what constraints can be derived from their early light curves. We use two sets of red supergiant (RSG) progeni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(98 citation statements)
references
References 73 publications
(151 reference statements)
4
94
0
Order By: Relevance
“…The dispersion could arise from intrinsic progenitor properties like the mass of the H envelope, the metallicity, the radius, or the characteristics of circumstellar material (CSM) around the progenitor. For example, in the last few years, several studies have shown that the majority of SNe II at early epochs present evidence of CSM interactions (e.g., Khazov et al 2016;Morozova et al 2016;Yaron et al 2017;Moriya et al 2017;Dessart et al 2017;Morozova et al 2017;Forster et al 2018). Moreover, some SNe II with strong CSM interaction have proven to be poor standard candles (de Jaeger et al 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…The dispersion could arise from intrinsic progenitor properties like the mass of the H envelope, the metallicity, the radius, or the characteristics of circumstellar material (CSM) around the progenitor. For example, in the last few years, several studies have shown that the majority of SNe II at early epochs present evidence of CSM interactions (e.g., Khazov et al 2016;Morozova et al 2016;Yaron et al 2017;Moriya et al 2017;Dessart et al 2017;Morozova et al 2017;Forster et al 2018). Moreover, some SNe II with strong CSM interaction have proven to be poor standard candles (de Jaeger et al 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…We trace the ionization fractions of hydrogen and helium solving the Saha equations in the non-degenerate approximation as proposed in Zaghloul et al (2000). The numerical grid consists of 1000 cells and is identical to the one used in Morozova et al (2015Morozova et al ( , 2016.…”
Section: Numerical Setupmentioning
confidence: 99%
“…Such stars have extended envelopes that typically contain several solar masses of hydrogen. Analytical calculations and numerical simulations of the light curves and spectra that would result from the successful explosion of such progenitor stars are able to reproduce the main features reasonably well, including the characteristic plateau in the light curve that is the defining signature of Type II-P SNe (Popov 1993;Filippenko 1997;Bersten et al 2011;Dessart et al 2013;Morozova et al 2016). Furthermore, searches for progenitors in pre-explosion images of Type II-P SNe indeed show the presence of presumably single red supergiants at the explosion site in several cases (Van Dyk et al 2003;Smartt et al 2009).…”
Section: Introductionmentioning
confidence: 90%